2005
DOI: 10.7863/jum.2005.24.3.349
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Aided Diagnostic Ultrasound Does Not Enhance Lung Metastasis in a Mouse Melanoma Tumor Model

Abstract: Objective. The purpose of this research was to test the hypothesis that contrast-aided diagnostic ultrasound (CADUS) could exacerbate the metastatic spread of mouse melanoma tumor cells to the lungs. Methods. The melanoma cell lines B16 and B16-D5 (metastatic specifically to lung) were implanted on a hind leg of female C57/bl6 mice. Growing tumors were scanned by 1.5-MHz diagnostic ultrasound in a 37°C water bath. Four hundred image frames were triggered at a 1-Hz rate with 4 retroorbital injections of an ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In a preclinical study, similar results were found for ablative exposures in a highly metastatic prostate cancer line, implanted into the hind leg of rats, where increases in the number of lung metastases were not observed [14]. Furthermore, lower diagnostic levels of ultrasound exposures were not found to enhance metastases [15, 16]. In contrast, a study using non-thermal, high-amplitude ultrasound exposures (on subcutaneous tumors implanted into the hind leg of mice) did show a significant increase in the number of lung metastases, when compared to diagnostic ultrasound exposures.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…In a preclinical study, similar results were found for ablative exposures in a highly metastatic prostate cancer line, implanted into the hind leg of rats, where increases in the number of lung metastases were not observed [14]. Furthermore, lower diagnostic levels of ultrasound exposures were not found to enhance metastases [15, 16]. In contrast, a study using non-thermal, high-amplitude ultrasound exposures (on subcutaneous tumors implanted into the hind leg of mice) did show a significant increase in the number of lung metastases, when compared to diagnostic ultrasound exposures.…”
Section: Introductionmentioning
confidence: 61%
“…Delaying or not amputating the tumor bearing leg would allow the primary tumor to seed additional metastases and increase metastatic burden, confounding the results and potentially resulting in detrimental effect on the health of the mice. [15, 16]. …”
Section: Discussionmentioning
confidence: 99%
“…At present, for various other studies, we routinely use the presented injection system for pre/post-CA T1w imaging and its success rate is now more than 90%. Retro-orbital injection has been reported an effective route to administer radioactive tracers for PET imaging (19) or microbubble contrast agents for ultrasonography (20) in mice. For our study, we chose the retro-orbital injection because pilot experiments with the same tumor mouse model showed that many tail vein injections failed, especially at later time points with progressed disease.…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous melanoma tumors in mice, which have an enhanced potential for lung metastasis, were scanned intermittently with 1.5 MHz DUS during or after DEFINITY injection (Miller and Dou, 2005). Subcutaneous melanoma tumors in mice, which have an enhanced potential for lung metastasis, were scanned intermittently with 1.5 MHz DUS during or after DEFINITY injection (Miller and Dou, 2005).…”
Section: Cedus Bioeffects In Other Tissuesmentioning
confidence: 99%